Focusing on dilemmas challenging reputation management in higher education. Issue 4 (6th May 2014) - Suomi, Kati; Kuoppakangas, Päivikki; Hytti, Ulla; Hampden-Turner, Charles; Kangaslahti, Jukka
Abstract : Purpose: – The purpose of this paper is to explore the dilemmas that challenge reputation management in the context of higher education (HE). Design/methodology/approach: – The paper introduces one Finnish multidisciplinary master's degree programme as a case in point. The empirical data comprises a student survey and semi-structured interviews with internal and external stakeholders whose work relates to the master's degree programme in question. Findings: – The findings identify different types of dilemmas arising from collaboration between stakeholders of HE. Practical implications: – The paper demonstrates how the dilemma-reconciliation method can be used to enhance reputation management in HE. Originality/value: – The novelty of the paper is in applying dilemma theory (Hampden-Turner and Trompenaars, 2000) in parallel with reputation theories. Dilemma theory attributes reputation risks to conflicting aims.